Non-Procedural Replacement of Constitutional Court Justices: A Threat to Democracy and Judicial Independence: Penggantian Non-Prosedural Hakim Konstitusi: Ancaman terhadap Demokrasi dan Independensi Peradilan - Sumodiningrat, Aprilian; Nabila Aulia Rahma (Jurnal Konstitusi, 2024)
The dismissal of Constitutional Court Justice Aswanto and the appointment of Guntur Hamzah as his replacement by the DPR, ratified by the President, have sparked public outcry over alleged violations of the Constitutional Court’s (MK) independence. This study aims to analyze the phenomenon of democratic regression and the erosion of MK’s independence resulting from the replacement of Constitutional Court Justices in violation of the Constitutional Court Law. The study addresses two main research questions: First, how does the non-procedural replacement of Constitutional Court Justices contribute to democratic regression? Second, what are the implications of such non-procedural actions by the DPR on the independence of the Constitutional Court? This research employs a doctrinal legal method, analyzing relevant regulations and literature. The findings reveal that, first, the non-procedural replacement of Constitutional Court Justices constitutes a symptom of constitutional backsliding that poses significant risks to democratic governance. Second, the independence of the MK’s judicial authority has been increasingly marginalized due to the non-procedural dismissal and appointment of Constitutional Court Justices, ultimately distorting the principle of checks and balances.